DURING THE COVID-19 PANDEMIC, SOUTH GARUT DEVELOPED A MARKETING PLAN FOR SANSEVIERIA ORNAMENTAL PLANTS - Frans Sudirjo; PA. Andiena Nindya Putri; Arief Yanto Rukmana; Etty Sri Hertini (SEAN Institute, 2023)
The research aims to formulate a marketing strategy for ornamental plant traders in Sansevieria, South Garut during the Covid-19 pandemic. The research method used is descriptive qualitative by identifying problems and analyzing them through internal and external factors. The analytical tools used are the SWOT Matrix and SWOT Quadrants. According to the results of the 'SWOT analysis' it can be determined that the business position of ornamental plant traders in Sansevieria is located in Quadrant 1 (0.52: 0.90). These results indicate that the business is in strengths and potential opportunities to be developed through an SO strategy or an aggressive strategy. The strategy formulation that can be implemented is by utilizing the location to increase market share, optimizing digital marketing through social media, marketplaces, and websites, then implementing a product bundling strategy, maintaining and improving product/service quality, cultivating Sansevieria bulan and other plant variants, and cooperate with banking services in providing capital for business development.